Cardiovascular magnetic resonance findings in Danon disease: a case series of a family - Liu, Xiaolong; Zhai, Ning; Wang, Xiaoqiang; Wang, Jiehuan; Jiang, Mengchun; Sun, Zhanguo; Chen, Yueqin; Xu, Jingjing; Cui, Yinghua; Li, Lu (Frontiers in Cardiovascular Medicine, 2023)
Background: Cardiac involvement constitutes the primary cause of mortality in patients with Danon disease (DD). This study aimed to explore the cardiac magnetic resonance (CMR) features and progressions of DD cardiomyopathies in a family with long-term follow-up. Methods: Seven patients (five females and two males), belonging to the same family and afflicted with DD, were enrolled in this study between 2017 and 2022. The cardiac structure, function, strain, tissue characteristics on CMR and their evolutions during follow-up were analyzed. Results: Three young female patients (3/7, 42.86%) exhibited normal cardiac morphology. Four patients (4/7, 57.14%) displayed left ventricle hypertrophy (LVH), and mostly with septal thickening (3/4, 75%). A single male case (1/7, 14.3%) showed decreased LV ejection fraction (LVEF). Nonetheless, the global LV strain of the four adult patients decreased in different degree. The global strain of adolescent male patients was decreased compared to the age-appropriate female patients. Five patients (5/7, 71.43%) exhibited late gadolinium enhancement (LGE), with proportion ranging from 31.6% to 59.7% (median value 42.7%). The most common LGE location was the LV free wall (5/5, 100%), followed by right ventricle insertion points (4/5, 80%) and intraventricular septum (2/5, 40%). Segmental radial strain (rs = −0.586), circumferential strain (r = 0.589), and longitudinal strain (r = 0.514) were all moderately correlated with the LGE proportions of corresponding segments (P <0.001). T2 hyperintense and perfusion defect foci were identified, overlapping with the LGE areas. During follow-up, both the young male patients exhibited notable deterioration of their cardiac symptoms and CMR. The LVEF and strain decreased, and the extent of LGE increased year by year. One patient underwent T1 mapping examination. The native T1 value was sensitively elevated even in regions without LGE. Conclusions: Left ventricular hypertrophy, LGE with sparing or relatively less involved IVS, and LV dysfunction are prominent CMR features of Danon cardiomyopathy. Strain and T1 mapping may have advantages in detecting early-stage dysfunction and myocardial abnormalities, in DD patients, respectively. Multi-parametric CMR can serve as an optimal instrument for detecting DD cardiomyopathies.